DEPRECIATION AND THE PRICE LEVEL. - Dohr, James L.; Paton, W. A.; Peloubet, Maurice E.; Bell, William H.; Greer, Howard C.; Kohler, Eric L. (The Accounting Review, 1948)
Abstract Six of the nation's outstanding accounting authorities have been invited to prepare papers expressing the views for and against the proposition that depreciation need not be restricted to the amortization of historical cost. While accountants have long realized that their basic standard of measurement, the dollar, is a varying one, they have, with one conspicuous exception, declined to recognize, as generally accepted accounting procedures, departures from cost because of changes in the purchasing power of money. In the list obstacles to good accounting is the misconception, often entertained, and blindly fostered by many accountants, that an income statement should reflect earning power or be confined to current operating performance. By moving depreciation expense up or down, according to predictions of the moment, a more accurate earning power or operating performance is said to be reflected in the net result. A good deal of mumbo-jumbo necessarily attaches to the process, for to them earning power or operating performance is a nebulous thing, visible only to initiates such as forceful corporate managements and accountants of discernment.